Accounts receivable outsourcing process, challenges and their mitigation plan in the context of Accenture Bangladesh - Kamal, Ainul (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.